Information System For Sale Of Muslim Clothes Based On E-Commerce Technology: Information System For Sale Of Muslim Clothes Based On E-Commerce Technology - M. Subchan; Dedi Setiadi (Jurnal Mantik, 2020)
The evolution that occurs on the internet is one of the most interesting phenomena in technological advancements that are happening now. One aspect that is arguably the main one in this evolution is the emergence of electronic commerce (e-commerce) in the business environment. E-commerce changes almost all the functions of the business area and every activity, from buying and selling to advertising. With the birth of E-commerce, it is easier for consumers to make buying and selling transactions without having to come to their place. Muslim clothes shop ayu fashion shops, established in 2012, is a shop that provides a variety of Muslim clothing. Muslim clothing that is sold in the ayu fashion shops stores includes several categories including Muslim, hijab, robe, and couple. The formulation of the problem in this study are (i) how to create information systems for selling Muslim clothing information systems assisted by e-commerce technology, (ii) How to test web-based ordering information media at ayu fashion Muslim clothing stores. The purpose of this study is (i) to create an information system for selling Muslim clothing information systems assisted by e-commerce technology, (ii) can produce web-based ordering information media testing at ayu fashion Muslim clothing stores. The research method used is a waterfall. Some conclusions that can be drawn from Muslim clothing stores and application of the system to the problems that exist in the design of e-commerce Information Systems at Muslim clothing stores ayu fashion shop are as follows: (i) Consumers can order products at these Muslim clothing stores anywhere that are connected with the internet network, consumers only need to register, log in, choose products and place an order, (ii) Designing an e-commerce in a Muslim clothing store ayu fashion shop can provide solutions to the problems faced by the ayu fashion shop Muslim fashion shop in the product sales process as well as product marketing solutions for companies, (iii) Testing of e-commerce information systems in Muslim clothing stores with results according to the needs or designs created.